2006
DOI: 10.1080/13576280500534693
|View full text |Cite
|
Sign up to set email alerts
|

Student attitudes towards communication skills training in a medical college in Western Nepal

Abstract: Communication skills training should be modified and strengthened. Formal courses during the clinical years are required. Training sessions for the faculty and further studies across different semesters and in different medical colleges in Nepal are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
80
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 20 publications
(13 reference statements)
16
80
4
8
Order By: Relevance
“…The PAS scores are comparable with the other studies, 7,10,11 however the NAS scores are very less than the scores of the medical students of Nepal, 11,12 Sri Lanka 13 and Iran. 10 These results may motivate the implementation of "communication skill training program" to the medical students, as positive attitude reflects caring patient orientation, thus a better health outcome.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The PAS scores are comparable with the other studies, 7,10,11 however the NAS scores are very less than the scores of the medical students of Nepal, 11,12 Sri Lanka 13 and Iran. 10 These results may motivate the implementation of "communication skill training program" to the medical students, as positive attitude reflects caring patient orientation, thus a better health outcome.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study there were no significant gender differences in the positive and negative attitude scores of the medical students. Though these results go contradictory to many previous studies done in UK, 7 Iran, 11 two studies -One on Nepal medical studentsl 11 and other on Srilankan medical students 13 observed a similar outcome. These controversial results suggest the need for more studies in the Indian context, in the future, that explores the gender difference in the attitude of medical students towards learning communication skills.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It also tests the mental attendance and the students' attitude towards patients. 6 Moreover, because OSPE questions are structured with marks to each point or instructions all the objectives of teachinglearning can be tested and each aspect can be assigned the desired weightage. 7 It also helps to minimize or prevent patient and examiner variability thus improving the validity of the examination.…”
Section: Introductionmentioning
confidence: 99%
“…Role plays have been used in other studies to impart breaking bad news, 8 and to teach students to communicate with simulated patients and provide drug and non-drug information. 9,10 In our module students were asked to do a role play on counselling couples to stress the cafeteria approach of counselling for contraception. The students were asked to enact two scenarios.…”
Section: Discussionmentioning
confidence: 99%